Renewable Energy: Novel Electrothermodynamic Power Generation (Adv. Energy Mater. 13/2015). Issue 13 (July 2015) - Kim, Yoonho; Kim, Juyoung; Yamanaka, Satoru; Nakajima, Akira; Ogawa, Takashi; Serizawa, Takeshi; Tanaka, Hirohisa; Baba, Masaaki; Fukuda, Tatsuo; Yoshii, Kenji; Takeda, Masatoshi; Yamada, Noboru; et al.
<x xml:space="preserve">Abstract</x> How can we convert exhaust heat from automobiles to renewable energy? In article number 1401942 Yoonho Kim, Hirohisa Tanaka, and co‐workers present an innovative electro‐thermodynamic cycle as an answer. The cycle is based on temporal temperature variations, the pyroelectric effect (instead of spatial temperature gradient), and the Seebeck effect, and the mechanism is investigated using operando time‐resolved synchrotron X‐ray diffraction. Practical energy and true energy breakeven are first achieved through real engine dynamometer experiments. Cover image by Remi Tanaka.